Discourse on the Absolute Competence of the State Administrative Court Post-Birth of Government Administrative Law - Valin Ismail, Nur; So Young, Choi (Estudiante Law Journal, 2025)
This paper analyzes the expansion of the absolute competence of the State Administrative Court (PTUN) based on Law Number 30 of 2014 and its consequences. Using a normative juridical method through literature research, the study finds that the expansion covers several aspects: a broader definition of decisions and government administration, including judicial, executive, and legislative actions, as well as factual acts; examination of administrative effort results; requests for positive fictitious decisions; review of abuse of authority; and testing of discretion. This expansion strengthens PTUN’s role in resolving administrative disputes and protecting public rights. However, it also brings consequences such as potential conflicts with administrative law theory, overlaps with criminal law in authority abuse cases, longer administrative procedures affecting access to justice, and challenges in regulating discretion due to complex legal issues.